Relational sacrifice across family relationships and contexts - Pippert, Hilary Dalton (Kansas State University, 2020)
The first study in this dissertation proposes and seeks to validate a new measure of relational sacrifice, the Relational Sacrifice Processes Scale (RSPS). Items were developed based on gaps identified through an extensive literature review and edited based on feedback from content experts. Through this process, a two-factor solution was hypothesized: active and passive. However, exploratory and confirmatory factor analyses yielded a three-factor solution. Through these analyses, the initial pool of 31 items was cut down to 20 total items across three subscales, identified as developing dependence, communication, and managing habits. Each of these concepts matches to themes existent within interdependence theory (Kelley & Thibaut, 1978, Rusbult & Buunk, 1993). The RSPS was designed to have wide-reaching applicability across a variety of family relationships and contexts, rather than solely being used to explore sacrifice within romantic relationships, a common shortcoming of current assessment tools. The second study operationalizes and tests a theorized model of sacrifice within family relationships; the model suggests that motivations to sacrifice, transformation of motivations to sacrifice, types of sacrifice, types of self-care, and family processes are all interrelated with bidirectional influence (Pippert et al., 2019). This model was operationalized and tested using a sample of adults with minor children who were coparenting apart (divorced, separated, etc.). A structural equation model was fit and demonstrated that one will be more likely to sacrifice in a relationship as they increase personal and relational efforts. One’s motivations to sacrifice and relationship quality were found to influence one’s relational sacrifice as well, providing partial support for the theorized model from Pippert and colleagues (2019). Faith and self-care practices at Wave 1 were directly related to relational sacrifice at Wave 1, while only faith practices were indirectly related to relational sacrifice at Wave 2. The third study validates the RSPS among the parent-child relationship, within a military family context. It specifically explores how motivations to sacrifice in a mother-child relationship moderate the effects of relational sacrifice on the mother, child, and family as a whole. Multi-group moderation was employed to determine how varying levels of motivation (high avoidance and high approach, low avoidance and low approach, or either high approach and low avoidance or low approach and high avoidance) influenced the relationships between relational sacrifice and the mother, child, and family as a whole. Moderation was found between relational sacrifice and each of the dependent variables. Results of these analyses suggest that those who were high in both approach and avoidance motivations demonstrated a more complete approach to sacrifice. Taken together these studies demonstrate that it may be meaningful to explore a holistic motivation to sacrifice, as compared to separating out distinct motivations, in studies exploring relational sacrifice processes. The RSPS can aid practitioners in helping their clients (within various relationships and contexts) understand that the self, the other, and the relationship are important to consider when striving to build successful and healthy relationships.
Keywords: Sacrifice; Interdependence Theory; Family Relationships